1988
DOI: 10.2337/diacare.11.6.495
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Glucose Tolerance in NIDDM by Clofibrate Randomized Double-Blind Study

Abstract: A randomized double-blind study was performed to examine the effect of clofibrate on glucose tolerance in subjects with non-insulin-dependent diabetes mellitus (NIDDM). Clofibrate (1.5 g/day) or placebo was administered to 70 patients and an oral glucose tolerance test (OGTT) was performed before and 12 wk after treatment. Blood glucose levels were significantly improved in clofibrate-treated groups at all time points during OGTT, whereas there was no change in insulin levels. Improvement of fasting glucose le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 13 publications
(18 reference statements)
2
47
1
Order By: Relevance
“…Based on these results, we conclude that in vivo activation of PPAR␣ preferentially modulates triglyceride metabolism without substantially affecting insulin sensitivity. This is consistent with clinical findings where therapeutic doses of fibrates reliably lower elevated triglycerides but produce variable, and/or subtle, effects on glucose metabolism (38,48,49).…”
Section: Resultssupporting
confidence: 87%
“…Based on these results, we conclude that in vivo activation of PPAR␣ preferentially modulates triglyceride metabolism without substantially affecting insulin sensitivity. This is consistent with clinical findings where therapeutic doses of fibrates reliably lower elevated triglycerides but produce variable, and/or subtle, effects on glucose metabolism (38,48,49).…”
Section: Resultssupporting
confidence: 87%
“…Clo®brate or acipimox, which decreases plasma NEFA concentration, improves glucose tolerance or insulin sensitivity in NIDDM patients. 27,28 Therefore, there is a possibility that the reduction in NEFA by YM268 is the driving force for the metabolic changes observed in this study. Further work will be necessary to examine this possibility.…”
Section: Discussionmentioning
confidence: 84%
“…The agonistic activity of KRP-101 in dog PPAR␣ transcriptional assay was Ͼ1,250-fold more potent than that of fenofibric acid, which is a major active metabolite of fenofibrate as a clinically relevant agonist. Whether fibrates are effective for glycemic control for type 2 diabetic patients has been controversial (16,20,23). In addition, there is no clear evidence supporting the clinical efficacy of fibrates for obesity and fatty liver (20,39).…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, it has been shown that PPAR␣ agonists prevent increases in adiposity and body weight in rodent disease models without reducing food intake (15). Fibrates often improve glucose intolerance in type 2 diabetic patients (16,23). However, the recent Fenofibrate Intervention and Event Lowering in Diabetes study in a larger number of subjects did not consistently show a pronounced effect on glucose levels in type 2 diabetic patients (20).…”
mentioning
confidence: 99%